Burnout and Work Stress of Nurses During the Covid-19 Pandemic - Nunung Rachmawati; Rahmanto, Tri Yuni (Future Science, 2024)
Introduction: Nurses are one of the frontline healthcare workers who are highly vulnerable to exposure to COVID-19. Physical and mental ex-haustion can be experienced by nurses working under the conditions of the COVID-19 pandemic. This exhaustion reflects the phenomenon of burnout. The prolonged COVID-19 pandemic in Indonesia also poses a risk of causing stress for all healthcare workers, especially nurses at Wonosari Regional General Hospital. Methods: This study was conducted to describe the levels of burnout and work stress among nurses at Wonosari Regional General Hospital dur-ing the COVID-19 pandemic. The research design used was quantitative with a descriptive-analytic approach.Results: The study found that nurses at Wonosari Regional General Hospital experienced burnout ranging from low to moderate levels, with none experiencing high levels of burnout. This could be attributed to the hospital's ability to meet the nurses' basic needs, such as adequate rest periods. Nurses at Wonosari Regional General Hospital experienced work stress ranging from mild to very severe levels. This could be due to the fear of contracting the virus, which poses a potential risk of death. The levels of burnout and work stress among nurses at the hospital varied, ranging from mild to very severe levels.Conclusion: This study provides hospital policymakers with an over-view of the condition of nurses during the COVID-19 pandemic, with the hope that the policies implemented can ensure safety and comfort, thereby reducing burnout and work stress among nurses during the pandemic.